Escafocefalias - Krivoy, Drs. Abraham; Krivoy, Mauricio; Krajewsky, Alejandro (Gaceta Médica de Caracas, 2021)
Se revisan 79 casos de escafocefalias de 144 casos de craneosinostosis recibidos en 10 años (79-89). La escafocefalia representó el 69,3% del total de craneosinostosis. Between 1979-1989, 114 of craniosynostosis cases were reviewed. Scaphocephaly were 79 cases (69.3%). Pre-operative EEG was performed en 84.8%; were abnormal 23.3% and 66.65 cases of this group improved.